INFORMATION TECHNOLOGY OF MANAGEMENT OF LEARNING LOAD IN INSTITUTIONS OF HIGHER EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
The article deals with the problems of the ICT development and application of the learning load management in institutions of higher education.
Keywords: curriculum; information and communication technologies; learning load